Extracellular vesicles secreted by bovine embryos produced in vivo and in vitro: miRNAs content and molecular effects in endometrial and luteal tissues - Bridi, Alessandra (2021)
Metabolic profiles, gene expression patterns, embryonic development, and the ability to establish and sustain early pregnancies are differences founded when in vivo- and in vitro- produced bovine embryos are compared. To the establishment of a successful pregnancy the perfect embryo-maternal communication is needed. Small extracellular vesicles (sEVs) are part of this crosstalk and carry bioactive molecules such as miRNAs that can act on target bovine cells within the reproductive system. Thereby, our hypothesis is that in vivo and in vitro bovine embryos secrete sEVs containing different miRNAs that can differentially modulate endometrial gene expression pattern and miRNAs profile in the corpus luteum (CL). To address this hypothesis, firstly, we investigated the miRNA content of in vivo and in vitro hatched blastocysts and in sEVs secreted by them. Day 9 in vivo or in vitro hatched blastocysts have distinct miRNA profiles. Small EVs secreted by them from day 7 up to day 9 of development contain different miRNAs. These miRNAs differently expressed are predicted to regulate pathways involved with early embryonic development and endometrial receptivity. Thereby, early embryo-maternal interactions can be modified and consequently can affect pregnancy success. Secondly, we investigated changes in the endometrial global transcriptome after the co-culture of endometrial explants with a day 7 in vivo or in vitro blastocysts. Differently expressed genes were identified in the endometrium and are associated with the embryo\'s presence or origin. Moreover, sEVs present in the conditioned media (C.M.) by these embryonic and endometrial cells contain different miRNAs, which are predicted to modulate the oxytocin signaling pathway. Finally, to understand if the communication among embryo, endometrium, and corpus luteum can be mediated by sEVs, luteal explants were treated with sEVs from C.M. by endometrial explants alone or cultured with a day 7 in vivo or in vitro blastocysts. MicroRNAs profile was modified in luteal explants treated with these sEVs, and we can observe an effect of the embryo presence and origin in these alterations. Together these results suggest that sEVs mediate early embryo-endometrium-corpus luteum communication, contributing to maintaining luteal viability and functionality. However, further experiments are needed to evaluate specific biological effects of these miRNAs carried by sEVs in the endometrium and in the corpus luteum. Moreover, the embryo origin (in vivo and in vitro) modify the interactions among embryo-endometrium-corpus luteum, suggesting strongly that these embryos have distinct needed to develop.